2004
DOI: 10.1007/s00330-004-2378-1
|View full text |Cite
|
Sign up to set email alerts
|

Near monochromatic X-rays for digital slot-scan mammography: initial findings

Abstract: X-ray spectra are composed of a broad bremsspectrum and anode-characteristic emission lines. In mammography typically molybdenum (Mo), rhodium (Rh) or tungsten (W) anodes are used in combination with Mo, Rh or aluminium filters. Only the photons with energies between 17 and 22 keV of the resulting spectrum are suitable for the soft tissue imaging needed for mammography. The aim of this article is to present first results obtained with a monochromator module mounted at the exit of the X-ray tube of a convention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Using a grid eliminates most of the scatter but also absorbs part of the primary radiation. When a slotscan method is used instead of a grid, more of the primary transmitted signal reaches the detector, with comparable low scatter fraction and an improved SNR quality [11,12]. For the slot-scan CCD system with CsI detector, better image quality has been shown as compared with conventional screen-film chest radiography [13,14].…”
Section: Discussionmentioning
confidence: 99%
“…Using a grid eliminates most of the scatter but also absorbs part of the primary radiation. When a slotscan method is used instead of a grid, more of the primary transmitted signal reaches the detector, with comparable low scatter fraction and an improved SNR quality [11,12]. For the slot-scan CCD system with CsI detector, better image quality has been shown as compared with conventional screen-film chest radiography [13,14].…”
Section: Discussionmentioning
confidence: 99%
“…Another distinguishing characteristic is the possibility to attach layers of HOPG to surfaces of almost arbitrary geometry. HOPG has been successfully applied, amongst others, as monochromator in prototypes of monochromatic slot scan mammography (Diekmann et al 2004) and its use in monochromatic enhanced radiation therapy has been investigated (Jost et al 2009).…”
Section: Hopg Mosaic Crystalsmentioning
confidence: 99%
“…A narrow energy spectrum can provide better contrast and significant dose reduction (Burattini et al , 1995; Boone and Siebert, 1994; Lawaczeck et al, 2005). The initial evaluation of a prototype digital mammography unit operating with a nearly monochromatic x-ray beam showed that the use of monochromatic slot-scan mammography resulted in correct identification of 93% of calcifications within a contrast-detail phantom (Diekmann et al , 2004). Clinical installation of monochromatic x-ray sources for mammography would require high-power x-ray tubes and imaging with the slot-scanning technique (Lawaczeck et al, 2005).…”
Section: Phantom Application: Beam Optimizationmentioning
confidence: 99%